2021
DOI: 10.1002/lary.29391
|View full text |Cite
|
Sign up to set email alerts
|

Tracheotomy Outcomes in 64 Ventilated COVID‐19 Patients at a High‐Volume Center in Bronx, NY

Abstract: Objectives/Hypothesis: The COVID-19 pandemic has resulted in a dramatic increase in the number of patients requiring prolonged mechanical ventilation. Few studies have reported COVID-19 specific tracheotomy outcomes, and the optimal timing and patient selection criteria for tracheotomy remains undetermined. We delineate our outcomes for tracheotomies performed on COVID-19 patients during the peak of the pandemic at a major epicenter in the United States.Methods: This is a retrospective observational cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 28 publications
3
25
1
3
Order By: Relevance
“…37 studies included mortality data, irrespective of subgrouping. Of the 3876 patients included across these 37 studies, 824 patients had died by the time of follow-up [24][25][26][27][28][29][30][31][32][33][35][36][37][38][39][40][41][41][42][43][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] . Only 14 studies explicitly reported a mean follow-up duration, giving a combined weighted mean of 42.03 days (SD 26.43) 24,26,27,30,33,37,42,43,48,50,52,56,…”
Section: Mortalitymentioning
confidence: 99%
See 3 more Smart Citations
“…37 studies included mortality data, irrespective of subgrouping. Of the 3876 patients included across these 37 studies, 824 patients had died by the time of follow-up [24][25][26][27][28][29][30][31][32][33][35][36][37][38][39][40][41][41][42][43][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] . Only 14 studies explicitly reported a mean follow-up duration, giving a combined weighted mean of 42.03 days (SD 26.43) 24,26,27,30,33,37,42,43,48,50,52,56,…”
Section: Mortalitymentioning
confidence: 99%
“…Heterogeneity was found to be substantial, with I 2 95% [95%CI 94.4%-96.4%](p < 0.0001; supplementary figure 2). Mean time to decannulation was reported in 19 of the 39 studies, identifying an overall weighted mean J o u r n a l P r e -p r o o f time from intubation to decannulation of 17.70 days (SD 11.31) [25][26][27][28][30][31][32][33]38,39,41,43,46,48,49,51,52,[55][56][57]60 .…”
Section: Decannulationmentioning
confidence: 99%
See 2 more Smart Citations
“…In their report of 64 ventilated patients undergoing tracheostomy for Coronavirus Disease of 2019 (COVID-19) respiratory failure, Ahmed and colleagues provide valuable insights into clinical outcomes and surgeon risk. 1 The findings emphasize how safety measures, patient selection, and data can improve care while mitigating harm. Their paper vividly illustrates the overwhelming concerns around healthcare professional safety that characterized the first wave of the pandemic.…”
mentioning
confidence: 99%